Pengaruh Pendapatan, Motivasi Kerja dan Disiplin Kerja terhadap Kinerja Guru Ekonomi SMA Negeri di Kabupaten Solok - Eka Putri, Desi Armi (Jurusan PIPS FKIP UMMY Solok, 2016)
Based on writer’s field research had shown that there are many still lower teacher’s teaching ability, because some factors which influence teacher’s teaching ability. This research purpose to describe income influence, working motivation, and teacher’s working dicipline toward economic teachers in SMA Negeri Solok.The kind of research which is used in this case is survey research. This research using quantitative approaciation. The population in this research is 28 teachers, meanwhile saturated sampling becomes its sample which intake is all of the population becomes as the sample.Analitycal result of data indicate that: (1) parsial influence coefficient in income band significant toward economic’s teachers work motivation Solok state senior high school is 39,0 %. (2) parsial influence coefficient in working motivation band significant toward economic’s teacher working dicipline in Solok state senior high school is 56,20 %. (3) parsial influence coefficient in income band significant toward teacher’s teaching ability directly is 53,3 %, menwhile parsial influence coefficient in income band indirectly toward work motivation variable and teacher’s dicipline is 13,85 %. Based on this research indicate that income, working motivation and working discipline are three important factor which influenced toward teacher’s teaching ability. It suggests to particular person such as: teachers and headmasters must pay attention for this three factor to increase teachers teaching ability.